PATHOLOGICAL ANATOMY OF BLOOD VESSELS OF PLACENTAL TISSUE OF PREGNANT WOMEN IN CORONAVIRUS INFECTION (American Journal of Interdisciplinary Research and Development, 2024)
This article aims to explore the complex landscape of placental vascular pathology in the setting of maternal COVID-19 infection, and to highlight the challenges and opportunities for clinicians, researchers, and health professionals in protecting pregnant women and their well-being.